2021
DOI: 10.1039/d1nr02389f
|View full text |Cite
|
Sign up to set email alerts
|

Caged structural water molecules emit tunable brighter colors by topological excitation

Abstract: Intrinsically, free water molecules are colorless liquid. If it is colorful, why and how does it emit the bright colors? We provided direct evidences that, when water was trapped into...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(63 citation statements)
references
References 57 publications
(70 reference statements)
9
54
0
Order By: Relevance
“…Recently, with the help of steady and transient absorption and emission spectrum, we unambiguously confirmed that SWs adsorbed or confined at nanoscale interface in the form of OH -•H 2 O could emit bright colors as non-conjugation luminophors [36][37][38][39] , which answers a century of debate on that water is colored or colorless liquid 40,41 . Differing from the traditional hydrogen bonding of water, the hydroxyl (hydroxide) groups and water molecules in structural water are mainly combined through the spatial interaction between the p orbitals of O atoms, which is a new kind of weak interaction with the characteristics of conjugated π bond and transient feature (Scheme 1c).…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Recently, with the help of steady and transient absorption and emission spectrum, we unambiguously confirmed that SWs adsorbed or confined at nanoscale interface in the form of OH -•H 2 O could emit bright colors as non-conjugation luminophors [36][37][38][39] , which answers a century of debate on that water is colored or colorless liquid 40,41 . Differing from the traditional hydrogen bonding of water, the hydroxyl (hydroxide) groups and water molecules in structural water are mainly combined through the spatial interaction between the p orbitals of O atoms, which is a new kind of weak interaction with the characteristics of conjugated π bond and transient feature (Scheme 1c).…”
Section: Introductionsupporting
confidence: 53%
“…Differing from the traditional hydrogen bonding of water, the hydroxyl (hydroxide) groups and water molecules in structural water are mainly combined through the spatial interaction between the p orbitals of O atoms, which is a new kind of weak interaction with the characteristics of conjugated π bond and transient feature (Scheme 1c). Very interestingly, when SWs are adsorbed onto the metal centers, due to the space interaction between the adjacent O atoms, a pair of chemical-sorption bonds of O-M (M could be different metals) perpendicular to the metal surface can be very quickly switched to two interface states or bonds parallel to the metal surface 37 , concomitantly accompanying the surface proton transfer (scheme 1c-e). The interaction between two O atoms on the interface is called p band intermediate or transient state (PBIS) by us 42 , which has typical π bond characteristics, and the interaction between two metal atoms is the well-known metallophilic interactions [43][44][45] , for example aurophilic interaction of Au-Au bonds 46 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that, in our previous report, after the vacuum evacuation, due to the removal of SWs with weak interactions, the blue emission at 440 nm of Ag NCs was quenched, and if trace amounts of water was re-added, the blue emission could be recovered (Yang et al, 2021). This probably accounts for why Ag 4 Au@DT NCs only captured one signal of chemically adsorbed water molecules with Ag + at 532.3 eV owing to high vacuum treatment during the XPS measurement, indicating the blue emissive SWs are weakly bonded on the fully core-shell structured Au-Ag bimetal Au NCs though water bridge, which strongly coordinated with Ag + (Figure 5C).…”
Section: Resultsmentioning
confidence: 78%
“…With the increase of Ag + dosing in the synthesis, the content of SWs interacting with Au atoms was significantly decreased, while a new chemically adsorbed species containing O atoms of Ag 0.5 Au@DT was produced at 532.3 eV, which was assigned to water coordinated with Ag + (Figure 4B, middle). If the Au core was completely covered by a thiolate-Ag + motif shell, only Ag + -H 2 O complexes were observed at 532.3 eV (Yang et al, 2021) (Figure 4B, bottom and Figure 5C).…”
Section: Resultsmentioning
confidence: 99%